Do Unions Matter? Trade Reform and Manufacturing Wages in South Africa - Shendy, Riham (2012)
The effect of nominal tariff cuts on industry wage differentials has been the subject of a number of recent empirical studies. In this paper, we investigate the latter relationship with respect to the South African trade reform experience using micro-level labour data for the period from 1995 to 2004. Our study extends on the existing literature in two respects: first, we are the first controlling for the potential effect of labour market institutions, such as collective bargaining power, in assessing the relationship between tariffs and industry wages. Second, we account for general equilibrium effects by controlling for the impact of changes in effective tariff rates. On the one hand, we find that only wages in industries with levels of unionisation beyond a certain threshold were adversely affected by tariff cuts. This negative effect is exacerbated by the extent of sectoral union power. The reported large magnitudes of the tariff impact on wages is in line with the considerably high mark-ups documented for South Africa. On the other hand we find some evidence suggesting that wages in industries with union power below the threshold were positively affected by the tariff cuts. This evidence suggests the omitted variable bias resulting from not controlling for industry heterogeneities in bargaining power when examining the wage-trade relationship.